Desarrollo de una solución de inteligencia de negocios para mejorar el proceso de toma de decisiones en el área de rentas de la Municipalidad Distrital de Moche - Lopez Vera, Euler Lanne (2020)
The main objective of this thesis is the development of a Business Inteligence solution to improve the decision-making procces in the Rents Area of the District Municipality of Moche. This document is divided into three specific objectives which are: Decrease generation reports time, decreace the cost of man-hours in the generation of reports and finally increasy the satisfaction level of the users of the proposal solution. This was a descriptive research with a population equal to the sample: forty reports and ten users. The validation of the instrument (inquest) was carried out under the Kendall test, and its reliability with the Alpha of Conbach; obtaining a 0.442 and a 0.824 respectively, demonstrating in such a way that there is concordance in the expert judgment and that the test is reliable. Regarding the results, a 32.56% increase in user satisfaction was obtained, a 69.12% reduction in time in the generation of reports and a 69% decrease in the costs of man hours that implies creating a report. In this way, it was concluded that the implementation based on Business Intelligence stimulates decision-making in the income area of the District Municipality of Moche.